Purification of Intensive Shrimp Farming Effluent by Gracilaria Coupled with Oysters - Junjing Li; Yu Xu; Yunlong Deng; Xiaojuan Hu; Haochang Su; Guoliang Wen; Yucheng Cao (Fishes)
In this study, we explored the ability of Gracilaria vermiculophylla coupled with Crassostrea hongkongensis to purify aquaculture effluent by analysing the purification of intensive shrimp farming effluent using G. vermiculophylla under different environmental conditions. After determining the optimal conditions, we further investigated the capability of the G. vermiculophylla and oyster coupling in intensive shrimp farming effluent purification. The shrimp farming density was 200 individuals per cubic metre (equivalent to 0.2 individuals per litre). The optimal environmental parameters were as follows: oyster biomass of 4.5 kg·m−3, G. vermiculophylla biomass of 2 kg·m−3, water temperature of 25–30 °C, and salinity of 15–30‰; the total inorganic nitrogen, PO43−-P, total nitrogen, and total phosphorus removal rates were 59.56%, 97.43%, 63.67%, and 76.25%, respectively, with G. vermiculophylla increasing in weight by 31.01%. For every 1 kg increase in the dry weight of G. vermiculophylla, 36.89 g of N and 12.40 g of P could be absorbed from the effluent. Our findings indicate that the coupling of G. vermiculophylla with oysters greatly contributed to the purification of effluent from intensive shrimp farming and can, thus, be used for treating intensive shrimp farming effluent.